(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Many times music and architecture have been associated, but much less often studies considered the social factors that intervened in the internal organization of the environments in which melodies were performed. Parties and banquets were always accompanied by instrumental melodies and, actually, this practice affected architecture both in Europe and in Middle East during Baroque Age.